Management and Performance in the Public Sector: Evidence from German Municipalities - Florian Englmaier; Gerd Muehlheusser; Andreas Roider; Niklas Wallmeier (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
We study management practices and performance in a representative sample of German municipalities, which provide the bulk of direct administrative services for citizens and firms in Germany. Surveyed municipalities differ substantially in their use of structured management practices, and this heterogeneity is also pronounced within all federal states, regional types, and population size brackets. Moreover, we document a systematic positive relationship between the degree of structured management and a diverse set of performance measures capturing municipalities' attractiveness for citizens and firms. Topic modelling (LDA) of survey responses suggests that the predominant management style is to use relatively little structured management.
Keywords: D20; D73; H11; H73; R50; 330; management practices; public sector organizations; local government; municipal performance; state capacity; World Management Survey (WMS)